Prospective feasibility study of a novel rigidizing stabilizing overtube in the resection of complex gastrointestinal polyps - Jawaid, Salmaan; Aboelezz, Ahmed F.; Daba, Gehad; Khalaf, Mai; Ayoub, Fares; Zabad, Noor; Mercado, Michael; Keihanian, Tara; Othman, Mohamed (Endoscopy, 2024)
Background A novel rigidizing overtube (ROT) was developed to facilitate endoscopic removal of complex gastrointestinal polyps. We aimed to prospectively evaluate the efficacy and safety of the device in the management of large gastrointestinal polyps.Methods A prospective, single-center study, conducted between May 2021 and April 2023, enrolled patients undergoing endoscopic resection of colon/duodenal polyps ≥25 mm. Primary outcomes were safety, technical success, and clinical success defined as the ability of ROT to facilitate endoscopic polyp removal without changing the initial resection method.Results 97 patients (98 polyps), with a mean polyp size of 33.2 mm (median 31.1), were evaluated. Technical and clinical success rates were 100% and 84%, respectively. Ileocecal valve location was the only predictor of clinical failure (P = 0.02). The mean time to reach the lesion was 7.2 minutes (95%CI 5–8), with overall resection and procedure times of 53.6 minutes (95%CI 48–61) and 88.9 minutes (95%CI 79–95), respectively. No device-related adverse events occurred. Lower technical (67%) and clinical (67%) success rates were seen for duodenal polyps (n = 6).Conclusion The novel ROT was safe, with high technical and clinical success during resection of complex colon polyps. Future studies will determine timing of implementation during routine endoscopic resection.